Azulene‐Fused Acenes - Ong, Albert; Tao, Tao; Jiang, Qing; Han, Yi; Ou, Yaping; Huang, Kuo‐Wei; Chi, Chunyan (Angewandte Chemie International Edition, 2022)
Non‐alternant non‐benzenoid π‐conjugated polycyclic hydrocarbons (PHs) are expected to exhibit very different electronic properties from the all‐benzenoid PHs. Herein, we report the synthesis and physical properties of three azulene‐fused acene molecules (1, 2 and 3), which are isoelectronic to the pentacene, hexacene and heptacene, respectively. X‐ray crystallographic analysis, NMR spectra, and theoretical calculations reveal a localised aromatic backbone comprising all the six‐ and five‐membered rings while the seven‐membered ring remains non‐aromatic. They display properties of both azulene and acenes and are much more stable than the respective acenes. The dications of 1, 2 and 3 were formed by chemical oxidation. Notably, 32+ exhibited an open‐shell diradical character (y0=30.2 %) as confirmed by variable‐temperature NMR and ESR measurements, which can be explained by recovery of aromaticity of an 2,6‐anthraquinodimethane unit annulated with two aromatic tropylium rings. Fusion of azulene to acenes of various length led to unexpected properties such as aromaticity and photophysical properties, and they are more stable than the respective isoelectronic acenes. Their dications showed aromaticity shift and one of them exhibited open‐shell diradical character.